Spawning Potential Ratio (SPR) Approach as a Management Measure of Skipjack Sustainability Record from Cilacap Fishing Port, Central Java, Indonesia - Yonvitner Yonvitner; Mennofatria Boer; Rahmat Kurnia (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
Highlight Research:Spawning potential ratio (SPR) based on the length and frequency data is a substitution approach for data-poor management in fisheriesGonad maturity is an indicator to ensure recruitment and stock sustainability. Therefore important to evaluate the impact of fishing capture on the size and length of fishSpawning potential ratio of skipjack relatively low and potential medium impact on risk sustainability AbstractWhen data is limited, management measurement from fisheries makes it possible to use natural history data to analyze the potential spawning ratio (SPR). This research aimed to determine skipjack fish management measure from the Indian Ocean landed at Cilacap Fishing Port through the SPR approach. The study was conducted in December 2014 to March 2015 using length and reproduction data. The analysis consisted of the size structure, growth rate, and asymptotic length that were analyzed using FISAT II program and length at fifty percent maturity (Lm50). The SPR analysis used SPR software from the application in http://barefootecologist.com.au/lbspr. The size distributions of skipjack obtained were a length of 220-790 mm and an average dominant length of 311-371 mm. The asymptotic length obtained was 831.57 mm, with growth rate and natural mortality of 1.1 and 1.44 per year respectively. The population proportion of 50% reaching gonad maturity (Lm50) was found at a length of 494.75 mm and (Lm95 = 522.39 mm) with an M/k ratio of 1.309. The length selectivity level was caught 50% (SL50 = 317.36 mm) and 95% (SL95 = 373.1 mm). The spawning potential ratio (SPR) ranged from 2-4 with an average of 4% during observation. The SPR potential, which is lower from the standardized threshold of 40%, indicates many young fish populations are caught, and the potential for overfishing is high, high risk, and low sustainability.